A Case of Pediatric Cyanoacrylate Adhesive Injury to the Eye - Aika Tsutsui; Kazunobu Sugihara; Masaki Tanito (Case Reports in Ophthalmology, 2020)
A 5-year-old Japanese boy presented to the emergency room of our hospital because his right eye had been glued shut for 2 h following instillation of cyanoacrylate adhesive. The clinical examination showed redness of the right upper and lower lid skin; the right eyelid margins adhered to each other because of matting of the eyelashes, and crystallized glue was found within the matted eyelashes. The “hook” technique, which separates the eyelids using a blunt-tip device, was performed to separate the lids. The technique seems to be simple and safe for physicians such as ophthalmology residents to use to treat cyanoacrylate-induced adhesion of the eyelids of patients who often first present to their local emergency room as in our case.